Gene Expression Data Analysis In Response to Nicotine Exposure: a Literature Study Revealing Differentially Expressed Genes In Biological Pathways - Azminah, Azminah; Munawwarah, Munawwarah (Journal of World Science, 2023)
This research aims to deepen our understanding of the effects of nicotine usage through a descriptive literature review, with the primary focus on exploring GEO DataSets via the analysis of Differentially Expressed Genes (DEGs) in response to nicotine exposure. The GEO DataSet search was obtained from the National Center for Biotechnology Information (NCBI) Gene Expression Omnibus (GEO), a relevant biomedical data source. The results of our investigation revealed a total of 11 GEO DataSets of Homo sapiens that met the inclusion and exclusion criteria for identifying Differentially Expressed Genes (DEGs). These datasets, namely GSE125217, GSE148812, GSE125416, GSE105445, GSE56398, GSE51284, GSE71795, GSE56383, GSE40689, GSE11208, and GSE11142, contained genes that underwent altered expression in response to nicotine exposure. The results of the gene analysis were further categorized based on their functional classifications. They encompass receptor genes such as CHRNA9, nAChRs, and TLR4, regulatory genes including CDK1, CHK1, ERBB2, EGFR, and E2F1, structural genes like H-Caldesmon, L-Caldesmon, SM22, CDH1/3, BDNF/NT-3, and MLL3, immunological genes such as TNF-?, IL-1?, IL-6, IL-10, MCSF, MCP-1, and ICAM-1, metabolic genes like CYP2A6 and APOE, and enzymatic genes such as PITRM1, DDR2, DHRS7, and SLC16A7. This review search provides a comprehensive insight into the molecular-level impact of nicotine, with potential implications for the development of treatment strategies and the discovery of relevant biomarkers associated with nicotine use.